PENGARUH KEPEMIMPINAN, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP DISIPLIN KERJA KARYAWAN DI SWALAYAN DEWI SRI MAGETAN - Sri Hartono (Juremi: Jurnal Riset Ekonomi, 2022)
The study aims to determine the effect of leadership, compensation and work environment on employee work discipline in the Dewi Sri Magetan supermarket. This type of research is a survey. Research subjects were 54 self-service employees. This data was collected by questionnaire and analized using multiple linear regression analysis. The result of the study show that : 1) leadership has a positive effect on employee work discipline with value tcount 3,645 > ttable 2,009with a significant 0,001. 2) compensation has a significant positive effect on employee work discipline with a tcount of 3,123 > ttable 2,009 with a significant of 0,003. 3) the work environment has a significant positive effect on employee work discipline with a value of tcaount of 3,547 > ttable 2,009 with a significant of 0,001. 4) Leadership, compensation, and work environment simultaneously effect employee work discipline with a fcount 12,668 > ftabel 2,56 with a significant 0,000. The contribution of leadership, compensation and work environment influence positively to employee work discipline by 48,1%. The regression equation obtained is Y= (-6,394) + 0,591 X1 + 0,431 X2 + 0,314 X3 + e.